Social conflict, heteroglossia and dialogic poema: situation for its discourse analysis (a critical return to Bakhtin and Voloshinov) - Casas, Arturo (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
This paper describes the tradition of sociological studies on the social conflict and its growing topicality, with an increasing presence in various areas of the social sciences. Subsequently, the analysis focuses on providing an outline of the heteroglossal-dialogic poem which deals with social conflicts, and it shows the pertinence of a critical return to the proposals of Bakhtin and Voloshinov regarding poetic enunciation and its possible modelling, for which alterity should be the required starting point.
Keywords: Bakhtin; dialogism; ethical act; heteroglossia; poetic enunciation; social conflict; sociology of literature; Voloshinov